Translating the Indigenous. Carl Strehlow’s Word for God in Central Australia - Anthony Pym (University of Leipzig, 2023)
The Lutheran missionary Carl Strehlow translated narratives of the Arrernte of Central Australia into German. In the first volume of his huge ethnographic study, published in 1907, he describes the Arrernte Altjira as a high god, arguing that the name should not be translated as “dreaming”, which is how most Australians understand the mythological primal time of First Nations cultures. Strehlow also implicitly justified the appropriation of Altjira as the name of his Christian god. The split between these two translations of Altjira became a confrontation between two networks that distributed trust in translations in very different ways. Although Strehlow offered no theory for his translation practice from Arrernte into German, his discourse can be understood as drawing on a nineteenth-century tradition of pedagogical translation, on the theory of natural religion expounded by the Lutheran Max Müller, and on the linguistic humanism of Wilhelm von Humboldt, which saw a common human aspiration in language, demanding respect for the words and ideas of the other, but also provided secular justification for the imposition of supposedly advanced cultural forms.